Oxytocin and Rodent Models of Addiction - Leong, Kah-Chung (Int Rev Neurobiol, 2018)
Interest for the use of oxytocin as a treatment for addiction began over 40years ago. Better known for its roles in parturition, lactation and pair bonding, oxytocin also has anxiolytic properties, reduces immune and inflammatory responses, and has a role in learning and memory. In this chapter, oxytocin effects on addiction processes are described by highlighting research findings that have used oxytocin within current preclinical animal models of addiction, relapse, or craving. First, we provide a brief background of the endogenous oxytocin system followed by descriptions of the behavioral models used to study addiction, including models of drug taking and seeking. Then we review recent preclinical studies that have used oxytocin as a therapeutic intervention throughout multiple stages of the addiction cycle from a behavioral and neurobiological perspective. These models encompass the entire range of the addiction cycle including acquisition and maintenance of drug taking, withdrawal and craving during periods of drug abstinence, and ultimately relapse. We then posit several theories about how oxytocin interacts with both drug and social reward, as well as presenting a mechanistic account of how specific oxytocin receptor localization may contribute to oxytocin’s efficacy as an addiction therapeutic.